Strategic corporate social responsibility : stakeholders in a global environment - Werther, William B.; Chandler, David , 1969- (SAGE, 2011)
Presenting the area of corporate social responsibility (CSR) as a constantly evolving field with direct impact on organizational strategies and success, this work links numerous subjects such as strategy, marketing and ethics, encouraging a multidisciplinary approach to this subject